Dead hand rule - Gladstone, Max (The craft wars, 2025)
"From the co-author of the viral New York Times bestseller This Is How You Lose the Time War.... Great powers clash and epic action unfolds in book three of the Craft Wars series. The time until the end-times is ticking away. If the world has any hope of surviving, it must come together now. The foundations of the world are quaking. Markets crash and cities burn as a new god struggles to be born. Ancient hunters skitter across space, eager and hungry. Dark forces conspire to undermine anything or anyone who could stand in their way. Divided, the world of the craft is certain to fall. In Alt Coulomb, the great powers of the world gather in conference. Empires, divinities, and corporate concerns take seats at the table. Untold wealth and inexhaustible might is on offer, but coalition will not come easily. Can these forces come together to save the world? And if they do, what parts of it will they choose to save, and for whom? Also Available by Max Gladstone: The Craft Sequence 1. Three Parts Dead 2. Two Serpents Rise 3. Full Fathom Five 4. Last First Snow 5. Four Roads Cross 6. Ruin of Angels The Craft Wars 1. Dead Country 2. Wicked Problems Last Exit Empress of Forever This is How You Lose the Time War (with Amal El-Mohtar)"-- Provided by publisher.